Screening for Penicillin G Acylase (PGA)-Producing Bacteria and Gene Cloning Using Degenerate Oligonucleotide Primed-PCR - Masdalifah, Masdalifah; Wulandari, Sri Rezeki; Sabbathini, Gabriela Christy; Ulfah, Maria; Achnafani, Dini; Wibisana, Ahmad; Sriherfyna, Feronika Heppy; Helianti, Is; Nurhayati, Niknik (Makara Journal of Science, 2025)
The growing concern over antibiotic resistance has driven global efforts to explore innovative solutions, including the use of Penicillin G acylase (PGA) to produce semisynthetic β-lactam antibiotics. This study screened four potential in-tracellular PGA-producing bacteria: Alcaligenes faecalis InaCC B444 (AfPGA), Kluyvera cryocrescens InaCC B850 (KcPGA), Providencia rettgeri InaCC B25 (Pr25PGA), and P. rettgeri InaCC B466 (Pr466PGA). Penicillin G Acylase encoding genes (pgas) were isolated from them using a Degenerate Oligonucleotide Primed-PCR (DOP-PCR) approach and sequenced. Microbiological assays confirmed all tested crude extracts to exhibit inhibitory effects. Penicillin G was used for evaluating hydrolytic activity and 6-Amino Penicillanic Acid (6-APA) coupled with D-p-Hydroxyl-phenylglycine methyl ester hydrochloride (DHPGME) for the synthetic activity. Pr466PGA and Pr25PGA showed the highest synthetic and hydrolytic activities, respectively. DOP-PCR successfully amplified a 2,517 bp pga-encoding Pr25PGA. The deduced amino acid sequence shared 95.1% identity with the known PGA from P. rettgeri PX04. Sec-ondary structure analysis of Pr25PGA revealed 35% α-helices, 16% β-sheets, and 49% coils, suggesting that the enzyme may be flexible and dynamic, with structural stability primarily provided by the α-helices and β-sheets. These findings offer valuable insights for the future design and application of Pr25PGA, particularly in the production of semisynthetic β-lactam antibiotics.